Correlates of physical function among stroke survivors: an examination of the 2015 BRFSS. (February 2018) - Ilunga Tshiswaka, D.; Seals, S.R.; Raghavan, P.
Abstract: Objectives: To identify the characteristics of stroke survivors with poor physical function. Study design: Cross-sectional. Methods: Secondary data analyses were performed with the 2015 Behavioral Risk Factor Surveillance System data set. Unadjusted and adjusted logistic regressions were employed to determine the correlates of poor physical function in stroke survivors. Self-reported difficulty with walking and stairs was used as a proxy for physical function. Characteristics such as age, race, sex, difficulty doing errands alone, difficult dressing or bathing alone, health care coverage, time since last routine checkup, and reported financial difficulty with regard to health care access were examined as contributing factors to physical function. Results: Approximately half of all stroke survivors reported having difficulty with walking and stairs (50.3%). As expected, the odds of reporting difficulty with walking and stairs were higher among stroke survivors aged 40 years and above (p < 0.0001). Interestingly, black/African American and multiracial respondents had higher odds of reporting difficulty with walking and stairs than whites, whereas Hispanic respondents had lower odds of reporting difficulty with walking and stairs than whites (p < 0.0001). Further analyses revealed that the disparity of physical function was preserved (p < 0.0001) after adjusting for age, race, sex, education level, family income, marital status, employment status, health insurance status, affordability of healthcare, and length of time from last doctor's visit. Conclusions: There were racial/ethnic disparities in physical function. Specifically, blacks/ African Americans had a 5.6% increase in the odds of reporting difficulty with walking and stairs than whites. Moreover, Hispanics reported significantly fewer problems than whites. Overall, similar sociocultural patterns in non-stroke and stroke populations were observed in this study. Highlights: Understanding reasons for racial disparities in physical function post-stroke can help mitigate some of the barriers. Implementing programs that will improve physical function in stroke survivors. Promoting accessible environment/housing that will facilitate mobility among non-stroke and stroke populations.